2021
DOI: 10.48550/arxiv.2102.13076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking and Survey of Explanation Methods for Black Box Models

Abstract: The widespread adoption of black-box models in Artificial Intelligence has enhanced the need for explanation methods to reveal how these obscure models reach specific decisions. Retrieving explanations is fundamental to unveil possible biases and to resolve practical or ethical issues. Nowadays, the literature is full of methods with different explanations. We provide a categorization of explanation methods based on the type of explanation returned. We present the most recent and widely used explainers, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 82 publications
(148 reference statements)
0
36
0
Order By: Relevance
“…Thus, algorithms that require gradients to discover counterfactual examples (e.g., like those in [9,56]) are not an option. We initially considered three gradient-free algorithms from the literature to search for counterfactual examples/explanations, namely Growing Spheres (GrSp) [34], LOcal Rule-based Explanations (LORE) [17] (these two have been used recently, e.g., in [3,36]), and the implementation of the Nelder-Mead method (NeMe) [13,43] by SciPy [55]. More details on these algorithms are given in Appendix B.…”
Section: Counterfactual Search Algorithmmentioning
confidence: 99%
“…Thus, algorithms that require gradients to discover counterfactual examples (e.g., like those in [9,56]) are not an option. We initially considered three gradient-free algorithms from the literature to search for counterfactual examples/explanations, namely Growing Spheres (GrSp) [34], LOcal Rule-based Explanations (LORE) [17] (these two have been used recently, e.g., in [3,36]), and the implementation of the Nelder-Mead method (NeMe) [13,43] by SciPy [55]. More details on these algorithms are given in Appendix B.…”
Section: Counterfactual Search Algorithmmentioning
confidence: 99%
“…Figure 1 of [38] suggests that in 2020 there were 400+ publications related to interpretability alone. The survey articles [1,8,38] provide systematic overview of the terminologies and the available techniques for different types of AI models for text, image, and tables. Some of the prominent techniques rely on the notions of feature importance [3], Shapley values [27], and counterfactual explanations [34].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, setting a proper visit order may lead to a better and intuitive understanding of the model prediction. There are papers in the published literature, where the BD method is used for post hoc model interpretability in a non-hierarchical learning setting 5,[34][35][36] . In this study, the BD results are discussed by referring to the BD data from our recent published work 37 , where the step-down method was used.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences were not discussed in sufficient detail. Rinzivillo et al also reported both SHAP and BD decompositions, but made a simple comparison on the feature importance plots from these methods without a further analysis about the differences 35 . Gosiewska and Biecek examined the dataset about the sinking of the Titanic using BD and SHAP.…”
Section: Introductionmentioning
confidence: 99%